Adult Learning Principles and Processes and Their Relationships with Learner Satisfaction: Validation of the Andragogy in Practice Inventory (API) in the Jordanian Context - Sunyoung Park; Petra Robinson; Reid Bates (Adult Education Research Conference, 2016)
This study aimed to assess the validity of the Andragogy in Practice Inventory (API) and to examine the relationships among adult learning principles and processes and learner satisfaction in Jordan. The results indicated that the API is a valid instrument and its components and learner satisfaction are positively related.
Keywords: Andragogy in Practice Inventory (API); adult learning; learner satisfaction